Economic growth and inequality of income distribution between regions: Evidence from Bali Province, Indonesia - Sukmaadi, Dewa Putu Sudibya; Marhaeni, A.A. Istri Ngurah (Journal of Socioeconomics and Development, 2021)
Bali Province shows a prominent performance in the development of the tourism sector. However, essential problems were found related to inequality in the distribution of income between regions. The aim of this study was to analyze the effect of locally-generated revenue, education spending, health spending, investment and infrastructure on economic growth and inequality in income distribution between districts/cities in the province Bali. This study uses a quantitative approach. The study explores panel data that combines time series and cross section data from the Regency / City of Bali Province during 2010 - 2017. The data analysis method uses path analysis. The results showed that local revenue, education spending, government spending on health, investment, and infrastructure had a positive effect on economic growth and reduced income inequality between regions. Economic growth is also able to mediate the influence of variables on inequality. The findings of this study emphasize the importance of planning coordination from each district and city to mutually commit to mobilizing all local resources such as human resources, finance, investment and infrastructure; to generate economic growth and reduce inequality between regions. JEL ClassificationÂ Â E27; H75; R58